2020
DOI: 10.1177/1066896920981633
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Large B-Cell Lymphoma and Renal Clear Cell Carcinoma as Collision Tumor: A Case Report and Review of the Literature

Abstract: Intravascular large B-cell lymphoma (IVLBCL) is a rare type of extranodal large B-cell lymphoma characterized by the selective growth of lymphoma cells within the lumina of vessels. The patient usually presents with nonspecific symptoms and a remarkable deterioration in performance status. The occurrence of synchronous IVLBCL and renal cell carcinoma (RCC) is extremely rare. A right kidney tumor was found in a 72-year-old man with a history of low back pain. The kidney was enlarged, with a tumor mass measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…9 Positive intravascular markers CD20, CD5, BCL-2, and BCL-6 are in support of the diagnosis of IVLBCL. 1,6,[13][14][15][16] Numerous studies reported that regarding patients with unexplained fever suspected of IVLBCL, RSB is suggested to be performed before other invasive tests because of its high sensitivity, less trauma, and operation being relatively simple. 8,17 For patients suspected of having IVLBCL, RSB is recommended before brain biopsy regardless of the involvement of central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…9 Positive intravascular markers CD20, CD5, BCL-2, and BCL-6 are in support of the diagnosis of IVLBCL. 1,6,[13][14][15][16] Numerous studies reported that regarding patients with unexplained fever suspected of IVLBCL, RSB is suggested to be performed before other invasive tests because of its high sensitivity, less trauma, and operation being relatively simple. 8,17 For patients suspected of having IVLBCL, RSB is recommended before brain biopsy regardless of the involvement of central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Both findings suggested abnormal DRU rather than physiologic renal activity 6 (Figure 2). The pattern of diffuse renal uptake was not only reported in MPA and other ANCA‐associated vasculitis (AAV), 7 but also in acute kidney injury 8 and intravascular B cell lymphoma 9,10 . All of the possible causes should be included in the differential diagnosis for DRU.…”
Section: Discussionmentioning
confidence: 99%
“…There have been only four cases of IVLBCL involving the microvasculature of RCC. [3][4][5][6] We present the case of a 69-year-old female who underwent RAPN for a clear cell RCC sized 1.7 cm, in which IVLBCL was incidentally detected. To our knowledge, this is the first case of synchronous IVLBCL with RCC detected by RAPN.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the synchronous occurrence of intravascular lymphoma with RCC is extremely rare. There have been only four cases of IVLBCL involving the microvasculature of RCC 3–6 …”
Section: Introductionmentioning
confidence: 99%